Criminal Legal Responsibility for Motorcycle Taxi Drivers as Narcotics Couriers - Romy Affandi Tarigan; Jaholden Jaholden; Ismail Koto (Lembaga Riset Mutiara Akbar, 2025)
This study examines the legal accountability of motorcycle taxi drivers who act as narcotics couriers in Indonesia. Using a normative juridical method with an analytical prescriptive approach, the research analyzes laws and regulations related to narcotics crimes, the criminal responsibility of drivers, and the juridical review of the Unaaha District Court Decision Number 132/Pid.Sus/2020/PN.UNH. The findings indicate that the driver was proven to have unlawfully distributed Class I narcotics under Article 114 paragraph (2) of Law Number 35 of 2009 on Narcotics. Although the driver initially claimed ignorance of the package contents, evidence from the trial demonstrated elements of intent or gross negligence. The study concludes that criminal liability depends on the driver’s awareness and intention; deliberate participation constitutes a punishable offense, whereas genuine unawareness may exempt the driver from liability. This research underscores the importance of assessing mens rea (intent) and actus reus (action) in determining accountability in narcotics-related offenses.